Analisis Kelayakan Usaha Laundry Koin Berbasis Teknologi di daerah Apartemen Podoromo City - Ramdan, Mohamad Fatur; Satrio, Fabyan Hijri; Zahra, Astri; Oktavianus , Yeriko Holman; Setyaningrum , Retno Purwani (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
The advancement of digital technology and the Internet of Things (IoT) has significantly transformed various service sectors, including the traditionally manual laundry industry. This study aims to evaluate the feasibility of Laundrify.Id, a coin laundry business based on IoT, to be implemented in Podomoro City Apartment, West Jakarta. The evaluation covers four major aspects: market potential, technical feasibility, financial viability, and socio-environmental impact. The research method used is a case study with a quantitative-descriptive approach. Primary data were collected through a survey of 100 apartment residents, while secondary data were obtained from literature reviews and analysis of similar businesses. The feasibility analysis includes Break Even Point (BEP), Net Present Value (NPV), Internal Rate of Return (IRR), Return on Investment (ROI), and SWOT analysis to identify the business's strengths, weaknesses, opportunities, and threats. The results show that 86% of respondents expressed interest in using Laundrify.Id, citing digital payment systems, 24-hour self-service access, and time efficiency as their main preferences. From a technical perspective, the use of IoT-enabled washing machines and QR code payment systems is considered effective and well-suited to modern living. Financially, the business is projected to reach BEP within five months, with a positive NPV of IDR 128.8 million and an IRR of 30%, indicating strong profitability and investment appeal. This study offers an original contribution by developing an empirical business model that integrates IoT, digital transactions, and sustainability principles. Furthermore, the model holds potential for replication in other urban areas with similar demographic and lifestyle characteristics.